الدراسة الفنية والاقتصادية لاستخدام طاقة الرياح ووحدات الديزل لتغذية أحمال مجتمع ريفي وأحمال السقاية لأراضي زراعية في المنطقة الوسطى لسورية - صبيح مسعود (Latakia University Journal -Engineering Sciences Series, 2019)
إن الهدف من هذا البحث هو شرح وتوضيح تقنية وحدات توليد الرياح والوضع الاقتصادي لإنجازها كحلول معاصرة بغية تأمين القدرة اللازمة لأحمال المجتمعات الريفية وأحمال السقاية للأراضي الزراعية. هذه المقالة تقدم دراسة متكاملة من الناحية الفنية والاقتصادية لتغذية الأحمال الكهربائية اللازمة لسقاية أراضٍ زراعية بمساحة 4000 [Hectares] تقع في المنطقة الوسطى لسورية في منطقة القصير الواقعة الى الجنوب الغربي من مدينة حمص بمسافة 25[Km]، بالإضافة الى تغذية أحمال أخرى ممثلة بأنشطة حياتية يومية يقوم بها المزارعون وأسرهم البالغ عددهم خمسة آلاف نسمة يسكنون في قرية نموذجية ضمن الموقع المدروس. في البداية تم حساب كمية المياه اللازمة للسقاية بطريقتي الري بالرذاذ والري بالتنقيط، الخطوة التالية كانت الدراسة التحليلية لمختلف الأحمال الكهربائية وتحديد متوسط القدرة اليومية للأحمال المطلوبة. قدم هذا البحث الدراسة الفنية لوحدات توليد طاقة الرياح100, 225, 300 and 500[KW] . شمل البحث أيضا الدراسة الاقتصادية لمنظومة العمل. من خلال هذا البحث تم التوصل إلى أن اختيار وحدات توليد الرياح ذو طابع اقتصادي ليس فقط في المناطق الريفية وإنما أيضا في أي موقع يوجد فيه سرعة رياح اقتصادية. The objective of this research work is to explain and illustrate the technology of wind generation units and their economic status as modern solutions aiming to insure the energy required to cover the loads of the rural communities and those for irrigation of the agrarian lands. This paper presents an integrated technical and economical study to supply the electrical loads required for irrigation of agrarian lands with an area of 4000[Hectares] located in the middle region of Syria, at Alkseir region 125[Km] south-west of Homs city, in addition to supplying other loads related to daily life activities of five thousands population of farmers families who live in typical villages within the studied site. This study included a stable work mechanism for the system employing an integrated energy generation system in the form of wind energy generation units and diesel generators. At the beginning we calculated the quantity of water needed for irrigation using both sprinklers and dripping systems, and the following step was an analytic study for different electrical loads along with determining the average daily power for the required loads. This paper has presented the technical study for the wind energy generation with capacities of 100, 225, 300 and 500[KW]. Besides, this work covered the economic study of the work system. Through this research, the choosing wind generation units is economically not only in rural sites but also in any site with economic wind velocity